Lipopolysaccharide induces apoptosis and oxidative cytotoxicity through stimulation of the TRPV1 channel in retinal pigment epithelium cell line - Alper, Ertuğrul (Journal of Cellular Neuroscience and Oxidative Stress, 2025)
Common and vision-threatening inflammatory ocular disorders are major issues on a global scale. The etiology and whole treatment for inflammatory disorders are yet unknown. With the exception of human retinal pigment epithelial-19 (ARPE-19), numerous cells have been shown to be involved in lipopolysaccharide (LPS)-induced free reactive oxygen species (ROS) and apoptosis through TRPV1 cation channel stimulation. I wanted to determine how TRPV1 affected the oxidative cytotoxicity and apoptosis caused by LPS in ARPE-19. Two main groups in the ARPE-19 cells were induced as control and LPS (1 g/ml for twenty-four hours). TRPV1 antagonist (100 M capsazepine (CAPZ) for 1 hour) blocked TRPV1 in the channel, whereas TRPV1 agonist (10 ⁭M capsaicin (CAPS) for 1 hour) stimulated cells of the main groups. The incubation of CAPS increased the amounts of apoptosis, caspases (caspase -3, -8, and -9), mitochondrial dysfunction, and ROS in the control and LPS groups, while CAPZ incubation diminished these amounts. However, their amounts were additionally increased in the LPS than in the control. LPS-induced increases of cell viability were diminished in the control and LPS groups by the CAPZ. In summary, CAPZ treatment through TRPV1 inhibition contributes to the oxidative stress and apoptosis that LPS causes in ARPE-19 cells. TRPV1 inhibition by CAPZ may be a viable treatment option for oxidative retinal damage induced by LPS.
Keywords: Hücresel Sinir Sistemi; Apoptosis; Inflammation; Retina oxidative injury; TRPV1 channel; Cellular Nervous System